Analisis Tingkat Kelelahan Pada Pengemudi Bus dan Mobil LV (Light Vehicle) di PT ABC - Chairun Nisa (Fakultas Rekayasa dan Teknologi Industri, 2025)
PT ABC, a coal mining company that operates an open-pit mining system, has a significant level of occupational safety risk, particularly in employee transportation activities. Fatigue experienced by bus and Light Vehicle (LV) drivers is a crucial factor that can potentially lead to accidents. This study aims to analyze the level of fatigue, identify dominant fatigue symptoms, and determine the contributing factors as well as the mitigation efforts among drivers in the company. The research used a quantitative and qualitative approach with the Industrial Fatigue Research Committee (IFRC) questionnaire distributed to 64 drivers consisting of 14 bus drivers and 50 LV drivers, supported by in-depth interviews. The results showed that the average fatigue score of bus drivers was 34.4 and LV drivers was 37.2, indicating that both groups were classified as experiencing mild fatigue. However, one LV driver was identified as experiencing moderate fatigue. The dominant fatigue symptoms reported by drivers included thirst, heavy legs, lower back pain, and difficulty concentrating. Environmental factors such as pothole road conditions and extreme weather were identified as the main causes of fatigue (27.6%), followed by mental workload (18.4%) and monotonous physical activities (17.1%). The most common effort taken by drivers to overcome fatigue was taking a short rest or sleep (54.7%). This study recommends several improvements, including providing drinking water facilities in vehicles, implementing routine stretching programs, and conducting regular vehicle inspections to reduce the risk of accidents caused by fatigue